The Role of Dynamic Autonomy Model and Teacher’s Participations to Foster Student’s Speaking Skill in Autonomous Learning Community - Lasmiatun, Ika; Hartono, Rudi (Universitas Negeri Semarang, 2020)
The aims of the research are to explain how is the role of Dynamic Autonomy Model, and how is the participations of teacher in fostering English speaking skill in order to know its practicality in autonomous learning community. The research was qualitative case study research that used interview, questionnaire, classroom observation, and document analysis in order to answer the research questions definitely. By using purposive sampling, twenty students and one English teacher were selected in gathering the data from the questionniare. Then five students and one teacher did the interview to get deeper understanding about the issue. The result shows the role of Dynamic Autonomy Model is usefull to give reflections and foster the students in planning, choosing materials and methods, completing task, monitoring, evaluation, managing their learning, dealing with feelings, motivating themselves, and coopertaing with other. Further, the participations of teacher is irresplacable as a guide, facilitator, organizer and designer, cooperator, inspirator and supporter, monitor and evaluator, resource supplier, and atmosphere creator. In higher education, teachers are facing unprecedented changes with often larger classes, more diverse students with diverse needs, demands from state, society, and employers, thus, teacher’s training should be conducted regularly so that the teacher is able to understand clearly what the participation and the strategies as well as the updated teaching methodologies to broaden his horizon